Peculiarities of usage distributed ledger technology in Russia - Bazarova E. A. (A breakthrough in science: development strategies, 2020)
the article is devoted to the study of the blockchain economy in the modern world, in particular their features of use. The study is based on statistical data from all over the world, and data on Russia are considered separately. The conclusions made in this paper, which reflect the General laws of the functioning of the blockchain, can find practical application in solving the problems of network effects in some sectors of the economy.
Keywords: Россия; Russia; цифровая экономика; блокчейн; digital economy; blockchain